Correlation of core stability with balance, agility and upper limb power in badminton players: a cross-sectional study - Ahmed, S.; Saraswat, A.; Esht, V. (Sport Sciences for Health, 2022)
Background Badminton is one of the most popular racket sports all over the world that requires powerful shorts, balance and agility performance, with core stability being the basic foundation on which optimum performance is built.